Description Of Body Mass Index In Diabetes Mellitus Patients In Mandiri Malau Malau Practice, Helvetia In 2021 - Imelda Derang; Linda Simorangkir; Louise Margaretha Sihombing (Sean Institute, 2022)
Background: Diabetes Mellitus is a disease caused by metabolic disorders in the pancreas organ and is characterized by an increase in blood sugar or often called a hyperglycemia condition due to a decrease in the amount of insulin from the pancreas. This study aims to determine the Body Mass Index in patients with Diabetes Mellitus in the independent practice of the midwife R. Malau Medan in 2021. Methods: The design of this study used a descriptive survey with a sampling technique of 60 respondents in the independent practice of the midwife R. Malau Medan. The instrument used in data collection is a questionnaire. Result: Data analysison the results of research conducted by researchers regardingthe height of diabetes mellitus patients in the Independent Practice of the midwife R. Malau Medan 2021, the majority of the height of 151 – 160 cm were 30 people (50.0%), and the minority >170 cm were 2 people (3.3%). Conclusion: The researcher recommends that the results of this study can be used as a reference and reference material in conducting further research. This study can increase knowledge and insight about body mass index with the incidence of diabetes mellitus. For further researchers, it is also recommended to choose a total sampling technique according to the conditions and characteristics of the population